Characterization of CYP3A pharmacogenetic variation in American Indian and Alaska Native communities, targeting CYP3A4*1G allele function. Issue 4 (27th January 2021) - Fohner, Alison E.; Dalton, Rachel; Skagen, Kasse; Jackson, Konner; Claw, Katrina G.; Hopkins, Scarlett E.; Robinson, Renee; Khan, Burhan A.; Prasad, Bhagwat; Schuetz, Erin G.; Nickerson, Deborah A.; Thornton, Timothy A.; et al.
Abstract: The frequencies of genetic variants in the CYP3A4 and CYP3A5 genes differ greatly across global populations, leading to profound differences in the metabolic activity of these enzymes and resulting drug metabolism rates, with important consequences for therapeutic safety and efficacy. Yet, the impact of genetic variants on enzyme activity are incompletely described, particularly in American Indian and Alaska Native (AIAN) populations. To characterize genetic variation in CYP3A4 and CYP3A5 and its effect on enzyme activity, we partnered with AIAN people living in two regions of Alaska: Yup'ik Alaska Native people living in the Yukon‐Kuskokwim Delta region of rural southwest Alaska and AIAN people receiving care at the Southcentral Foundation in Anchorage, Alaska. We identified low frequencies of novel and known variation in CYP3A4 and CYP3A5, including low frequencies of the CYP3A4*1G and CYP3A5*1 variants, and linkage disequilibrium patterns that differed from those we previously identified in an American Indian population in western Montana. We also identified increased activity of the CYP3A4*1G allele in vitro and in vivo. We demonstrated that the CYP3A4*1G allele confers increased protein content in human lymphoblastoid cells and both increased protein content and increased activity in human liver microsomes. We confirmed enhanced CYP3A4‐mediated 4β‐vitamin D hydroxylation activity in Yup'ik people with the CYP3A4*1G allele. AIAN people in Alaska and Montana who carry the CYP3A4*1G allele—coupled with low frequency of the functional CYP3A5*1 variant—may metabolize CYP3A substrates more rapidly than people with the reference CYP3A4 allele.